Titanium dioxide nanoparticles enhance the detrimental effect of polystyrene nanoplastics on cell and plant physiology of Vicia lens (L.) Coss. & Germ. seedlings - Spanò, Carmelina; Giorgetti, Lucia; Bottega, Stefania; Muccifora, Simonetta; Ruffini Castiglione, Monica (Frontiers in Plant Science, 2024)
Polystyrene nanoplastics and titanium dioxide nanoparticles are widely spread in all environments, often coexisting within identical frameworks. Both these contaminants can induce negative effects on cell and plant physiology, giving concerns on their possible interaction which could increase each other’s harmful effects on plants. Despite the urgency of this issue, there is very little literature addressing it. To evaluate the potential risk of this co-contamination, lentil seeds were treated for five days with polystyrene nanoplastics and titanium dioxide nanoparticles (anatase crystalline form), alone and in co-presence. Cytological analyses, and histochemical and biochemical evaluation of oxidative stress were carried out on isolated shoots and roots. TEM analysis seemed to indicate the absence of physical/chemical interactions between the two nanomaterials. Seedlings under cotreatment showed the greatest cytotoxic and genotoxic effects and high levels of oxidative stress markers associated with growth inhibition. Even if biochemical data did not evidence significant differences between materials treated with polystyrene nanoplastics alone or in co-presence with titanium dioxide nanoparticles, histochemical analysis highlighted a different pattern of oxidative markers, suggesting a synergistic effect by the two nanomaterials. In accordance, the fluorescence signal linked to nanoplastics in root and shoot was higher under cotreatment, perhaps due to the well-known ability of titanium dioxide nanoparticles to induce root tissue damage, in this way facilitating the uptake and translocation of polystyrene nanoplastics into the plant body. In the antioxidant machinery, peroxidase activity showed a significant increase in treated roots, in particular under cotreatment, probably more associated with stress-induced lignin synthesis than with hydrogen peroxide detoxification. Present results clearly indicate the worsening by metal nanoparticles of the negative effects of nanoplastics on plants, underlining the importance of research considering the impact of cotreatments with different nanomaterials, which may better reflect the complex environmental conditions.